Black-Start Scheme Evaluation Based on Improved ELECTRE Method and Comprehensive Weight - Yinxing XIANG; Jikeng LIN (Zhongguo dianli)
The scientificity and rationality of a black-start scheme directly affects the rapidity and effectiveness of system recovery. Therefore, it is particularly important to select an optimal black-start scheme from multiple feasible restoration options through evaluation. An evaluation method is proposed based on combination of comprehensive weight method and improved ELECTRE method, and applied to evaluation of black-start schemes. Firstly, the comprehensive weight is obtained by combining the objective weight and expert weight according to a certain proportion, of which the objective weight is obtained by traditional entropy weight method, and the expert weight of evaluation indexes is obtained by ratio scale method. Then, the qualitative index of the black-start evaluation scheme is described using triangular fuzzy number and 1-9 scale method, and then it is combined with the ELECTRE method, which overcomes the drawback that ELECTRE method cannot adapt to the evaluation of qualitative indexes and is solely dependent on the expert weight. The proposed method in this paper realizes the reasonable combination of subjective weight and objective weight, and improves the ELECTRE method, which makes the evaluation of black-start scheme more convenient and the obtained results more reasonable. Finally, a case study has verified the validity and correctness of the method.